Image_10.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The skill of making bhakris is passed down through generations of Kolis, from mother to daughter and other female family members, who usually do the cooking at home. During marriage negotiations, the worthiness of a Koli bride is judged by her ability to prepare the perfect round bhakri.